2012
DOI: 10.1111/j.1470-6431.2012.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Manual dishwashing process – a pre‐assigned behaviour?

Abstract: Global studies have observed many techniques of manual dishwashing causing different levels of performance and using quite different amounts of water, energy, time and detergent. It is not known, however, if these techniques are pre‐assigned to a person and persist when dishes are washed under different conditions, or are adapted to the specific type of dish‐cleaning process. Here we explored this question in a study with 40 test subjects selected equally from Germany and East European countries by asking them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…This kind of response indicates that the awareness to conserve water not necessarily depict the real‐life practice by the participants. In compliance with Gillessen et al (Gilleßen, Berkholz, & Stamminger, ), this survey also indicated that consumers' manual dishwashing practice is somewhat a preassigned behavior. For instance, when asked about the resource dosage, the overall response percentage for “more fat—increase water temperature” was detected to be quite low (31%).…”
Section: Discussionsupporting
confidence: 72%
“…This kind of response indicates that the awareness to conserve water not necessarily depict the real‐life practice by the participants. In compliance with Gillessen et al (Gilleßen, Berkholz, & Stamminger, ), this survey also indicated that consumers' manual dishwashing practice is somewhat a preassigned behavior. For instance, when asked about the resource dosage, the overall response percentage for “more fat—increase water temperature” was detected to be quite low (31%).…”
Section: Discussionsupporting
confidence: 72%
“…Richter [30] observed that the percentage of dishes pre-rinsed before loading was as low as 4% in Germany, and as high as 42% in Italy, a practice related perhaps to force of habit, ingrained by observing parental behaviour from childhood days [84], for instance, for East European test participants and by [10] for Greek households, habituated to running-tap manual washing instead of using the soak-in-sink method), or an empirically derived lack of complete trust in the ability of the dishwasher to render good-quality output, irrespective of the degree of soiling of the load of dishes [3]. However, if pre-rinsing is deemed to be important, the dishwasher's 'rinse/rinse and hold' option which could be taken advantage of, and the purpose served with a much lower water footprint too [30].…”
Section: Manual Alternative or Complementmentioning
confidence: 99%
“…Less water would entail its requirement at a higher temperature and more time spent with manual input. Gillessen and co-authors [84] observed that even if 'dS' was changed, test participants, in general, did not seem to change the input-mix conspicuously (save the German participants, who used a lot more time when the dS was increased). In many countries, the factor 'energy' is not available [6], and washing is often done with only room-temperature water, necessitating greater inputs of time and, to some extent, detergents and water.…”
Section: Manual Alternative or Complementmentioning
confidence: 99%
“…Following this conclusion, it seems now to be possible to compare different hand dishwashing procedures regarding their microbiological reduction factors by just defining the way the washing is done in ap recise procedure as done in this study.A sd ishwashing by hand was found to be done very different from consumer to consumer and from country to country [25 -28] this will allow to judge these differences also regarding their hygienic aspects. Additionally,the here presented procedure may be used in laboratory studies were \ normal" consumers are asked to clean soiled dishes under controlled conditions, like in [25,27,28].…”
Section: Soiling Agent Spinach Ricementioning
confidence: 99%